2014
DOI: 10.1186/1471-2393-14-144
|View full text |Cite
|
Sign up to set email alerts
|

Geophagy practices and the content of chemical elements in the soil eaten by pregnant women in artisanal and small scale gold mining communities in Tanzania

Abstract: BackgroundGeophagy, a form of pica, is the deliberate consumption of soil and is relatively common across Sub-Saharan Africa. In Tanzania, pregnant women commonly eat soil sticks sold in the market (pemba), soil from walls of houses, termite mounds, and ground soil (kichuguu). The present study examined geophagy practices of pregnant women in a gold mining area of Geita District in northwestern Tanzania, and also examined the potential for exposure to chemical elements by testing soil samples.MethodWe conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
78
2
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 28 publications
8
78
2
6
Order By: Relevance
“…These levels of Hg might be lower in the end product as the metal has the tendency to evaporate during the firing process because of high volatility of Hg at higher temperatures. However, other studies reported as high as 2.4 µg/g, 1.4 µg/g and 1.5 µg/g of Hg in Accra, Abidjan and Nigeria, geophagy clays, which are eaten directly 7 , as well as a mean of 0.53 µg/g in clay deposits in Vume in the Volta region of Ghana 5 and a mean concentration of 0.046 µg/g of Hg in geophagy soil in Tanzania 6 .…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…These levels of Hg might be lower in the end product as the metal has the tendency to evaporate during the firing process because of high volatility of Hg at higher temperatures. However, other studies reported as high as 2.4 µg/g, 1.4 µg/g and 1.5 µg/g of Hg in Accra, Abidjan and Nigeria, geophagy clays, which are eaten directly 7 , as well as a mean of 0.53 µg/g in clay deposits in Vume in the Volta region of Ghana 5 and a mean concentration of 0.046 µg/g of Hg in geophagy soil in Tanzania 6 .…”
Section: Resultsmentioning
confidence: 90%
“…These levels were within the safe levels of 80.0 µg/g 17 . One study observed a mean of 6.5 µg/g of Pb in geophagy soil in Tanzania 6 , while another study also reported 27.70±2.90 µg/g of Pb in geophagic white clay at Abuakwa in the Ashanti region of Ghana 18 . The lead levels in the samples from Mankessim were lower than the levels reported from other regions, where the clay is eaten directly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The determination of both essential and toxic elements present in the clay soil commonly consumed by pregnant women, in order to assess safety, has been recently carried out, for example, in Tanzania by Mwalongo and Mohamed (2013) and Nyanza et al (2014) and in Nigeria by Lar et al (2014), Igeoma et al (2014) and Owumi and Oyelere (2015). Kikouama and Baldé (2010) to compensate eventual dietary deficiencies in Fe and Zn have designed clay-containing pellets bearing certain Fe and Zn amounts; such pellets were able to be retained for few hours by flotation in the highly acidic stomach cavity in order to favour and optimize the controlled release and gastrointestinal absorption of those essential trace elements.…”
Section: Geophagy (Or Geophagia)mentioning
confidence: 99%
“…The types of earth materials consumed vary from one locality to the other. Nyanza et al [18] reported that pregnant women in Tanzania preferred soil from the wall of houses, termite mounds and ground soil but commonly (69%) eat soil sold in the markets. And other studies reported that most of the geophagists (95%) purchase it from the markets [19; 20].…”
Section: Introductionmentioning
confidence: 99%